(untitled) (Gestão & Regionalidade, 2015)
This paper aims to understand and analyze the field and focus of study on repatriation, promoting a discussion based on specific literature review. The motivation of this research comes from some precariousness in the emphasis to this stage of the process given by academic studies. Having the organization as field of study, the reviewed studies reinforce the practices and roles on a universalistic approach and, afterwards, aggregate the perspective of differentiation between size and moment of the company. In most cases, they are theoretical propositions, which have not been tested. On the other hand, the studies that emphasize the individuals reinforce individual nuances and changing processes, questioning the organizational practices, challenging the adoption of the Universalistic approach. Subjects such as knowledge (retention and management) and ROI were little discussed by this paper due to the few references available, but will be key to the future of the field.